2008
DOI: 10.2139/ssrn.2894310
|View full text |Cite
|
Sign up to set email alerts
|

Value-at-Risk and Expected Shortfall When There Is Long Range Dependence

Abstract: Empirical studies have shown that a large number of financial asset returns exhibit fat tails and are often characterized by volatility clustering and asymmetry. Also revealed as a stylized fact is Long memory or long range dependence in market volatility, with significant impact on pricing and forecasting of market volatility. The implication is that models that accomodate long memory hold the promise of improved long-run volatility forecast as well as accurate pricing of long-term contracts. On the other han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Cardamone and Folkinshteyn (2007) study the sensitivity of U.S. interest rates and exchange rates. Härdle and Mungo (2008) focus on the value-at-risk of some stock indexes. McMillan and Kambouroudis (2009) compare the predictions of the HYGARCH model and other models for 31 stock indexes.…”
Section: Presentation Of the Semifarma-hygarch Modelmentioning
confidence: 99%
“…Cardamone and Folkinshteyn (2007) study the sensitivity of U.S. interest rates and exchange rates. Härdle and Mungo (2008) focus on the value-at-risk of some stock indexes. McMillan and Kambouroudis (2009) compare the predictions of the HYGARCH model and other models for 31 stock indexes.…”
Section: Presentation Of the Semifarma-hygarch Modelmentioning
confidence: 99%
“…Nevertheless, empirical studies have revealed that long memory GARCH (LM-GARCH) models are very successful in accurately forecasting the conditional volatility of asset returns and often outperform short memory GARCH type models (see, among others, Giot andLaurent, 2003, Degiannakis* (2004), Tang andShieh, 2006, Grané andVeiga (2008), Härdle and Mungo (2008), Morana, 2009, Demiralay andUlusoy, 2014 and Aloui and Ben Hamida, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…So far there is no consensus which model or method is the most suitable for forecasting VaR and ES. Nevertheless, empirical studies have revealed that long memory GARCH (LM-GARCH) models are very successful in accurately forecasting the conditional volatility of asset returns and often outperform short memory GARCH type models (see, among others, Giot andLaurent, 2003, Degiannakis* (2004), Tang andShieh, 2006, Grané andVeiga (2008), Härdle and Mungo (2008), Baillie and Morana, 2009, Demiralay and Ulusoy, 2014and Aloui and Ben Hamida, 2015.…”
Section: Introductionmentioning
confidence: 99%